The Effect of Eco Enzyme Concentration and NPK Fertilizer Dosage on the Growth and Yield of Sweet Potatoes (Ipomoea batatas L.) at the Urban Farming Planting System - Dzikrika, Ferziana Nurmeilinda; Sitawati, Sitawati; Aini, Nurul; Damaiyanti, Dewi Ratih Rizki (International Journal of Environment, Agriculture and Biotechnology, 2023)
This research was conducted at Malang during rainy seasons from february until June 2023. The purpose of the study is to obtain optimum tuber yields by applying eco enzyme concentration and NPK fertilizer dosage through agronomic experiments in urban farming systems. The research used Factorial randomized block design. Eco enzyme concentration (E) as First factor: E0 = 0 ml.l-1, E1 = 15 ml.l-1, E2 = 30 ml.l-1, E3 = 45 ml.l-1. The second factor, NPK = (P) NPK fertilizer dose, namely: P1 = 3.75 g plant-1 NPK, P2 = 5.62 g plant-1 NPK, P3 = 7.50 g plant-1 NPK. This research was repeated three times. The results showed Eco enzyme concentration treatment affects the dose of NPK fertilizer on sweet potato plants. At an NPK fertilizer dose of 3.75 g plant-1, the highest fresh tuber weight was produced at an eco enzyme concentration of 30 ml l-1. At NPK fertilizer doses of 5.62 and 7.50 g plant-1, the fresh weight of tubers was the same at all eco enzyme concentrations. The optimum eco enzyme concentration in the NPK fertilizer dose treatment of 3.75 g plant-1 was 27.05 ml l-1, 5.62 g plant-1 was 25.44 ml l-1 and 7.50 g plant-1 was 26.54 ml l-1. eco enzyme concentrations and NPK doses can increase the growth and yield of sweet potato plants, on the variables: leaf area, plant dry weight, tuber fresh weight, harvest index.